Impaired SIRT1 nucleocytoplasmic shuttling in the senescent heart during ischemic stress. Issue 11 (28th September 2012) - Tong, Chao; Morrison, Alex; Mattison, Samantha; Qian, Su; Bryniarski, Mark; Rankin, Bethany; Wang, Jun; Thomas, D. Paul; Li, Ji
Abstract : A "longevity" gene, sirtuin 1 (SIRT1), can attenuate age‐dependent induction of left ventricular dysfunction. This study aimed to characterize the role of SIRT1 in the tolerance of aged heart to ischemic insults. Male C57BL/6 young (4–6 mo) and aged (24–26 mo) mice were used to determine the role of SIRT1 in myocardial ischemia/reperfusion (I/R) tolerance. SIRT1 localization was assessed by confocal microscopy. Immunoblotting was used to evaluate SIRT1 expression and translocation. The results demonstrated that SIRT1 is expressed predominantly as a sumoylated form in cardiomyocyte nuclei. Moreover, cardiac overexpression of desumoylase, sentrin‐specific protease 2 (SENP2), significantly reduces nuclear sumoylated SIRT1 levels ( P <0.05). Interestingly, I/R stress leads to desumoylation and translocation of nuclear SIRT1 into the cytoplasm in aged but not in young hearts. SIRT1 activity in ischemic young hearts was 3.2‐fold higher than that seen in ischemic aged hearts, which suggests that aging causes impaired nucleocytoplasmic shuttling and activation of SIRT1 during ischemic stress. The infarct size in aged and Sirt1 +/– knockout hearts was higher than that observed in young and Sirt1 +/+ WT littermate hearts, respectively (all P <0.05). SIRT1 agonist, SRT1720, reduced myocardial infarction in both aged and Sirt1 +/– hearts. Therefore, impaired cardiac SIRT1 activity plays a critical role in the observed increase in susceptibility of the aged heart to I/R injury. SIRT1 agonist can restore this aging‐related loss of cardioprotection.— Tong, C., Morrison, A., Mattison, S., Qian, S., Bryniarski, M., Rankin, B., Wang, J., Thomas, D.P., Li, J. Impaired SIRT1 nucleocytoplasmic shuttling in the senescent heart during ischemic stress. FASEB J . 27, 4332–4342 (2013). www.fasebj.org